Revision of the subgenus Phortica (sensu stricto) (Diptera, Drosophilidae) from East Asia, with assessment of species delimitation using DNA barcodes - Huang, Jia; Gong, Lu; Tsaur, Shun-Chern; Zhu, Lin; An, Keying; Chen, Hongwei (Zootaxa, 2019)
A total of 50 (43 known and seven new) species in the subgenus Phortica (sensu stricto) were surveyed and (re)described from China: P. bicornuta (Chen & Toda, 1997); P. bipartita (Toda & Peng, 1992); P. biprotrusa (Chen & Toda, 1998); P. cardua (Okada, 1977); P. chi (Toda & Sidorenko, 1996); P. conifera (Okada, 1977); P. eparmata (Okada, 1977); P. eugamma (Toda & Peng, 1990); P. excrescentiosa (Toda & Peng, 1990); P. fangae (Máca, 1993); P. flexuosa (Zhang & Gan, 1986); P. foliata (Chen & Toda, 1997); P. gamma (Toda & Peng, 1990); P. gigas (Okada, 1977); P. glabtabula Chen & Gao, 2005; P. hainanensis (Chen & Toda, 1998); P. hongae (Máca, 1993); P. huazhii Cheng & Chen, 2008; P. iota (Toda & Sidorenko, 1996); P. jadete Zhu, Cao & Chen, 2018; P. kappa (Máca, 1977); P. lambda (Toda & Peng, 1990); P. latifoliacea Chen & Watabe, 2008; P. magna (Okada, 1960); P. okadai (Máca, 1977); P. omega (Okada, 1977); P. orientalis (Hendel, 1914); P. pangi Chen & Wen, 2005; P. paramagna (Okada, 1971); P. perforcipata (Máca & Lin, 1993); P. pi (Toda & Peng, 1990); P. protrusa (Zhang & Shi, 1997); P. pseudopi (Toda & Peng, 1990); P. pseudotau (Toda & Peng, 1990); P. psi (Zhang & Gan, 1986); P. rhagolobos Chen & Gao, 2008; P. saeta (Zhang & Gan, 1986); P. setitabula Chen & Gao, 2005; P. subradiata (Okada, 1977); P. tau (Toda & Peng, 1990); P. uncinata Chen & Gao, 2005; P. unipetala Chen & Wen, 2005; P. allomega Gong & Chen, sp. nov.; P. archikappa Gong & Chen, sp. nov.; P. dianzangensis Gong & Chen, sp. nov.; P. imbacilia Gong & Chen, sp. nov.; P. liukuni Gong & Chen, sp. nov.; P. tibeta Gong & Chen, sp. nov.; and P. xianfui Gong & Chen, sp. nov. In addition, seven new synonyms were recognized: P. acongruens (Zhang & Shi, 1997), syn. nov.; P. antillaria (Chen & Toda, 1997), syn. nov.; P. kukuanensis Máca, 2003, syn. nov.; P. linae (Máca & Chen, 1993), syn. nov.; P. shillongensis (Singh & Gupta, 1979), syn. nov.; P. takadai (Okada, 1977), syn. nov.; and P. watanabei (Máca & Lin, 1993), syn. nov. A key to all Asian species (except for the eparmata species complex) of this subgenus was provided. All currently available DNA barcode (partial mitochondrial cytochrome c oxidase subunit I (COI) gene) sequences of this subgenus (217 sequences of 54 species) are employed in a molecular analysis using different species delimitation methods. The results indicate that approximately 68.5% (37 of 54 spp.) of Phortica (s. str.) species could be clearly distinguished from closely related morphospecies or cryptic species.